Mechanical Performance of Salvadora Persical (Miswak) Reinforced Polylactic Acid Matrix Composites for Three Dimensional Printing - Kartal, Fuat; Kaptan, Arslan (Black Sea Journal of Engineering and Science, 2023)
This study examines the mechanical performance of polylactic acid (PLA) matrix composites reinforced with Salvadora Persica (Miswak). With the increasing use of environmentally friendly materials, researchers are focusing on the production of biodegradable materials. However, incompatibility between PLA and filler materials used in PLA composites causes mechanical problems during production. This study deals with the production and characterization of PLA composites containing lignocellulosic and inorganic fillers using maleic anhydride grafted polylactic acid (PLA/g/MA) as a matrix. The aim of the research is to examine the mechanical specifications of Miswak powder reinforced PLA composites and to evaluate their suitability for practical applications. PLA was used as the matrix material and PLA/g/MA was used as the compatibilizer. Composites containing Miswak powder at different weight concentrations (5%, 10%, 15% and 20%) were characterized using scanning electron microscopy along with tensile and bending tests. The obtained results showed that different Miswak concentrations affect the mechanical specifications of the composites. Composites at 5% concentration demonstrated excellent interlayer adhesion and high mechanical strength, demonstrating favorable mechanical specifications. The findings show that Miswak powder is a potential filling material to improve the mechanical specifications of PLA composites and provide antimicrobial benefits. The results of this study shed light on the mechanical performance of Miswak reinforced PLA matrix composites, which are promising for 3D printing applications. In addition, it is stated that the materials used, such as natural filling materials, contribute to the development of sustainable and environmentally friendly materials by reducing the environmental impact.
Keywords: Material Design and Behaviors; Malzeme Tasarım ve Davranışları; Salvadora Persica; Miswak powder; Polylactic acid; PLA composites; Mechanical specifications; D printing; 12. Responsible consumption